Pengaruh Model Problem Based Learning Berbasis Etnosains terhadap Hasil Belajar IPA di Sekolah Dasar: Tinjauan Literatur - Haifa Sakinah; Elfia Sukma; Inggria Kharisma (Indo-MathEdu Intellectuals Journal, 2026)
Science education faces challenges in the form of low student learning outcomes due to the use of learning models that do not actively engage students and have not yet connected the material to the local cultural environment. An alternative that can be applied is the ethnoscience-based Problem Based Learning (PBL) model. This study aims to analyze the effect of the ethnoscience-based PBL model on science learning outcomes in elementary schools based on published research findings. The research method used is a literature review by examining various scientific articles obtained from Google Scholar, Sinta and other relevant sources from the period 2016–2026. The article criteria included studies discussing the implementation of the ethnoscience-based PBL model in science learning at elementary schools. The data analysis technique used was descriptive analysis, which presents findings from various studies systematically and critically without conducting in-depth statistical analysis. The review results show that the ethnoscience-based PBL model has a positive effect on elementary school students’ science learning outcomes, as seen in their conceptual understanding, critical thinking skills, and problem-solving abilities. Therefore, the ethnoscience-based Problem Based Learning model is suitable as an alternative innovation in elementary science learning to improve student learning outcomes. Thus, it is recommended that teachers and curriculum developers integrate ethnoscience into science learning, especially in topics related to students’ local environment and culture